Identification Insertion/Deletion 6bp of 3’-Untranslated Region Thymidylate Synthase Gene in Orbital Region Basal Cell Carcinoma - Lady Kavotiner; Ibrahim Ibrahim; Irsan Saleh (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2015)
Background: Basal cell carcinoma (BCC) is the most common eyelid malignancy tumor. The risk factor for development of BCC related to environtmental factor especially prolonged sun exposure and individual factor. One of the internal risk factor contributes to BCC development is genetic instability including defects in folic acid synthesis or DNA synthesis. Enzyme participates in this process is 3’-untranslated region Thymidylate synthase gene (UTR TS). This study is to identify the insertion or deletion of 6bp of 3’-UTR TS gene in orbital region BCC. Methods: This study was a descriptive explorative study with case series which involved 13 orbital region basal cell carcinoma (BCC). The diagnosis was based on histological examination of the tumor. The frequencies of insertion/deletion 6bp of 3’-UTR TS gene were assessed by Polymerase Chain Reaction (PCR) and restriction fragment length polymorphism (RFLP) analyses using Dra I as restriction enzyme. Results: Thirteen patients consist of 9 males (69%) and 4 females (31%). Majority of subjects have history of sun exposure. The most common type of BCC is nodular type (80%). There was two subject with recurrent case. Identification result of insertion/deletion 6bp 3’-UTR TS gene found heterozigot mutant -6bp/+6bp in 7 samples (54%) at 152bp band and 158 bp band, homozigot mutant -6bp/-6bp in 6 samples (46%) at 152bp band. Conclusion: The results of this study were 7 samples (54%) are heterozigot mutant -6bp/+6bp and 6 sample (46%) are homozigot mutant -6bp/-6bp.